Aplastic Anemia in Children - Widayat Widayat; Sunarto Sunarto; Sutaryo Sutaryo; M. Zurghiban; Ismangoen Ismangoen (Paediatrica Indonesiana, 1983)
During a period of 5 years (1975-1980) nine children with aplastic anemia were admitted to the Department of Child Health, Gadjah Mada University Hospital, Yogyakarta. They were 6 boys and 3 girls from 4 to 12 years of age. Of all the patients. 7 could be classified as the acquired type, and 2 as the idiopathic type. Generally, they were admitted with the following chief comptlaints: paleness, weakness and bleeding manifestations (skin bleeding 100%, bleeding of mucous membrane 44.4%). All of them showed pancytopenia. Eight patients showed normocytic normochromic anemia and one patient had microcytic hypochromic anemia. Seven patients had aplastic bone marrows, the other two hypoplastic. All patients received prednison and oxymetholon. Only one got remission after getting therapy for eight months. Six of nine patients died (66,6%). Four of the six death were caused by bleeding (44.7%) and two others might be caused by sepsis and bleeding (33.3%).